Integration of Islamic Values in Digital Business Ethics: a Case Study of Social Media Use by Muslim Business Actors - K, Masnama; Irwandi, Irwandi; Nengsih, Hijrana; Arifin, Asriadi (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2025)
The development of digital technology has changed the paradigm of modern business, including among Muslim entrepreneurs who now utilize social media as a primary means of promotion and transactions. However, this dynamic raises ethical challenges that need to be examined from the perspective of Islamic values. This study aims to analyze how Islamic values such as amanah , sidq , 'adl , ta'awun , and maslahah are integrated into digital business ethics. The method used is a qualitative approach through literature study, with descriptive-thematic analysis of relevant academic literature. The results show that the application of Islamic values in digital activities plays a significant role in building consumer trust, creating spirituality-based business sustainability, and fostering social responsibility in the digital economy ecosystem. The implications of this study emphasize the need to develop Islamic digital business ethics guidelines and increase ethical literacy for Muslim entrepreneurs to be able to carry out fair, blessed, and sustainable business practices in the era of digital transformation.